Pemikiran Islam Kontemporer (Muhammad Baqir Al-Sadr, Ibrahim Umar Vadillo, M. Umer Chapra) - Arofiani Mutmainah; Habibah Ramadhani Nasution; M. Syawal Pitriyadi; Fitri Hayati (Journal Of Business, Finance, and Economics (JBFE), 2025)
This research discusses the thoughts of three contemporary Islamic figures—Muhammad Baqir al-Sadr, Ibrahim Umar Vadillo, and M. Umer Chapra—in the field of Islamic economics. Muhammad Baqir al-Sadr offers an economic system based on monotheism with an emphasis on fair distribution of wealth and multi-level ownership as an alternative to capitalism and socialism. Ibrahim Umar Vadillo criticizes the use of paper money and advocates the re-implementation of the gold dinar and silver dirham to create monetary stability based on intrinsic value. Meanwhile, M. Umer Chapra develops an Islamic economic approach based on maqashid sharia to realize welfare and social justice, and criticizes the materialistic conventional economy. The thoughts of these three figures not only offer solutions to global economic inequality, but are also relevant to be applied in efforts to build a more just and sustainable economic system in the modern era.